UJI BAKTERIOLOGIS LENGKUAS GILING (Alpinia galanga L.) YANG DIJUAL DI PASAR RAYA KOTA PADANG - Aryani, Ika; Indriati, Gustina; Nurmiati, Nurmiati (Pendidikan Biologi, 2013)
ABSTRACTGalangal is one of spices for cooking. Galangal ussually sold in the form of minced ginger, galangal added by water in milling  process water, as ussual the processing merchant of  galangal do not wash it by running water, and do not wash the equipment with clean water. Bacteria contamination  in the food still can occured. In the process the galangal added by water to much and preparation  often contact with humans and equipment in every steps. This study aims to conduct bacteriological testing ground galangal (Alpinia galanga L.) which sold in Pasar Raya Padang. Types of research used in this research is descriptive research, by looking at the presence or absence of Escherichia coli and coliform bacteria in the sample of milled galangal. The method used to determine the bacteriological quality of minced Galangal is the MPN method which consists of three step: the estimation test, confirmation test and test assertion perfection. This research was conducted at the Laboratory of Natural Sciences Andalas Univercity. The results showed in the prediction test almost samples are positive it also occure in confirmation test and the test of perfection. Index of Escherichia coli and Coliform MPN found sel/100 0-96 and 4.4-240 ml. Based on this study can be suggested to traders of milled Galangal can be milled to maintain cleanliness during processing and storage of it, and recommended to the citizen should select the galangal wich will bought. And also need to do further testing to determine the classification of coliform bacteria were obtained.